Theoretical Study on the Thermoelectric Properties of Porous Armchair Graphene Nanoribbons - Navjotkaur; Randhawa, Deep Kamal Kaur; Kaur, Sukhdeep (Asian Journal of Electrical Sciences, 2019)
Thermoelectric properties of porous graphene nanoribbons (GNRs) have been explored for a range of pore dimensions in order to achieve a high performance one-dimensional nanoscale thermoelectric device. In this paper, study has been done to observe the effect of different nanoporous shapes and their associated positions on the thermoelectric properties of GNRs. The aim of this work is to study the effect of various circular, triangular, rectangular and rhombus shape dimensions so as to tune the pore to its optimal dimension that would enhance the overall thermoelectric efficiency. Further, the effect of passivation of pore edges has been studied for all shapes so as to observe its effect on thermoelectric performance. Also, the effect of temperature dependence on thermoelectric efficiency has been studied. Ballistic transport regime and semi empirical method using Huckel basis set is used to obtain the electrical properties while the tersoff potential is used for the phononic system.